“WE JUDGE THE PRESENT BY THE PAST”: THE CROWNING OF PHYSICAL EDUCATION BY SPORTS - Juliana Martins Cassani; Amarílio Ferreira Neto; Lucas Oliveira Rodrigues de Carvalho; Wagner dos Santos (Cadernos de Pesquisa, 2019)
Abstract This article analyzes orientations for teaching sports published in journals about the teaching and techniques of physical education from the period 1932-1960, using as sources the Revista de Educação Física [Journal of Physical Education] and Educação Physica [Physical Education]. The theoretical-methodological basis for the article was the analysis of the materiality of printed. The sources indicate a body of knowledge needed to teach physical education, related to a project of professional education. The conditions for crowning physical education in schools include the need to study, corporally appropriate the exercises, mediate interpersonal relations, and know the rules and history of sporting practices, to maintain the depth and complexity required for the organization of their educational programs.